KEMISKINAN DAN KETENAGAKERJAAN DI JAWA BARAT: STUDI KASUS KABUPATEN PURWAKARTA - Wicaksono, Bayu Rhamadani; Kharisma, Bayu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2020)
The problem of poverty is a complex and multidimensional problem which covers various aspects in the human life, not least for local governments in the scope of West Java. The efforts to alleviate poverty must pay attention to the root problem of poverty itself. One of the strategic issues in the Regional Medium-Term Development Plan/ Rencana Pembangunan Jangka Menengah Daerah (RPJMD) 2018-2023 is poverty and employment. The purpose of this study is to analyze the relationship of poverty and employment in West Java in 2017-2018 with a case study in Purwakarta Regency. The data used are secondary data from district/municipality in West Java in the 2014-2017 period using panel data regression analysis with the Random Effects Model (REM) and the results are as follows. First, the Open Unemployment Rate/ Tingkat Pengangguran Terbuka (TPT) has a positive but not significant impact on poverty levels. Second, the number of workers in wholesale, retail, restaurant and hotel sectors has a negative and significant impact on poverty levels. Third, the number of casual workers in agricultural sector has a positive and significant impact on poverty levels.